Analysis of Microbial Community in the Archaeological Ruins of Liangzhu City and Study on Protective Materials - Sun, Mingliang; Zhang, Fengyu; Huang, Xinduo; Han, Yeqing; Jiang, Nan; Cui, Biao; Guo, Qingling; Kong, Mengyue; Song, Lin; Pan, Jiao (Frontiers in Microbiology, 2020)
This study aims to provide a reference for the protection of the Archaeological Ruins of Liangzhu City. As a basis for the further preservation of these artifacts, it was necessary to ana-lyze the microflora colonizing these soil objects. To this end, samples with microbial character-istics were obtained and analyzed by SEM and metagenomic sequencing to reveal the composi-tion of the microflora. In addition, culture-dependent approaches were employed to complement the data obtained by amplicon sequencing. Finally, we carried out degradation experiments on the protective materials commonly employed at the earthen sites at present and used Fourier infrared spectroscopy to test and analyze the biodegradability of the protective materials. Soil samples containing protective materials were analyzed to test the influence of protective mate-rials on soil properties.